muliati muliati - Muliati, Muliati; Sabani, Fatmarida; Amin, Muh Agil (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
This study is a Research and Development (R&D) project using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects were teachers and seventh-grade students. Data were collected through observation, interviews, questionnaires, and documentation. The developed learning media, a pop-up book, focused on the Islamic jurisprudence (Fikih) topic of purification from hadas and najis. The results indicate that the media development process followed the five ADDIE stages, obtaining avalidity score of 85% from media experts and 95% from material experts, both categorized as highly valid. Practicality tests showed an average of 89% from students and 94% from teachers, categorized as highly practical, with aspects of content, efficiency, and interactivity reaching 100%. Therefore, the developed pop-up book is considered highly valid and practical for supporting Fikih learning.